2021
DOI: 10.1002/chem.202005427
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Solar Thermal Batteries through Combination of Magnetic Nanoparticle Catalysts and Tailored Norbornadiene Photoswitches

Abstract: Cobalt catalysts are immobilized on the surface of iron oxide nanoparticles for the preparation of highly active quasi‐homogeneous catalysts toward an efficient release of photochemically stored energy in norbornadiene‐based photoswitches. The facile separation of the iron oxide nanoparticles through exploitation of the intrinsic magnetic properties of this material enables efficient cyclization of energy storage and release. Through the transition from cobalt (II) salphen to cobalt porphyrins, a 22.6‐fold inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 52 publications
1
37
2
1
Order By: Relevance
“…The experimental setup consisted of three NMR tubes which were equipped with a 15.9 mM solution of each NBD‐NDI‐hybrid 5 a – c in toluene‐d 8 , respectively. Previous studies, performed in our working group, indicated that toluene was the most suitable solvent with respect to side‐reactions, reaction rate and solubility [11] . All three NBD‐NDI hybrids were irradiated with an UV‐LED emitting at 310 nm in a custom‐build photoreactor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental setup consisted of three NMR tubes which were equipped with a 15.9 mM solution of each NBD‐NDI‐hybrid 5 a – c in toluene‐d 8 , respectively. Previous studies, performed in our working group, indicated that toluene was the most suitable solvent with respect to side‐reactions, reaction rate and solubility [11] . All three NBD‐NDI hybrids were irradiated with an UV‐LED emitting at 310 nm in a custom‐build photoreactor.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on NBD systems revealed a direct correlation between increasing concentrations and rising quantum yields of the investigated samples. [11]…”
Section: Photoswitching Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of photoswitches to effectively store as well as release solar energy has rendered them ideal candidates in the development of molecular solar–thermal (MOST) materials . These include norbornadienes, dihydroazulenes, and azobenzene-based , photoswitches as well as fulvalene diruthenium-based complexes . Of the photoswitches, those containing azo linkages have been championed for their low cost, ease of synthesis and derivatization, and cycle stability .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) are valuable tools for an increasing number of applications [ 1 , 2 , 3 ]. MNPs have found an important role in the biomedical sciences, e.g., cell sorting [ 4 , 5 ], therapeutics and drug delivery [ 6 , 7 , 8 , 9 , 10 , 11 ], cell transfection [ 12 ] and magnetic resonance imaging (MRI) [ 13 , 14 , 15 ] and in various technologies, e.g., separation [ 16 , 17 ], sensing [ 1 , 18 , 19 , 20 , 21 ], material development [ 22 , 23 , 24 , 25 , 26 , 27 ], including use in templated nanogel synthesis [ 28 , 29 ], and catalysis [ 30 , 31 , 32 ]. Iron oxide is the most commonly used material for MNP fabrication due to its ready availability, ease of use in synthesis, relatively low toxicity and chemical and mechanical stabilities [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%